Implementation Teaching at the Right Level (TaRL) Approach to Improve Learning Outcomes of X IPA 2 SMAN 2 Labuapi - Anggriani, Shintya Putri; Handayani, Baiq Sri; Hadratullaili, Hadratullaili (Universitas Islam Negeri Mataram, 2023)
Learning by using an approach that is in accordance with student characteristics will greatly affect student learning outcomes, so an approach that suits the learning needs and abilities of students is needed. One approach that can be used by considering the ability level of students is the TaRL (Teaching at the Right Level) Approach. TaRL is a learning approach that does not refer to the class level, but refers to the ability level of students. TaRL can be the answer to the problem of the ability gap that has been happening in the classroom. Teachers must know how the level of students' abilities so that they can provide appropriate learning based on these abilities. Thus, knowledge becomes easier for students to understand so that learning outcomes will improve. This study aims to improve the learning outcomes of students in class X IPA 2 by applying the TaRL approach. This research method is a class action research with the stages of planning, implementation, observation, and reflection. Data analysis techniques in this study used qualitative and quantitative analysis. The research results of the application of TaRL in cycle 1 reached 70.00, from the reflection data of cycle I, additional peer tutor treatment was given in cycle II, so that the results of cycle II increased to 85.00, this shows that the application of the TaRL approach in the learning process can improve the learning outcomes of students in class X IPA 2 on ecosystem material.